Structural Model Analysis of Emotional Intelligence and COVID-19 Anxiety with the Mediating Role of Perceived Social Support and Social Cohesion in University Students - Babaali, Zahra; Karimi Dashtaki, Ahmad; Eslami, Mahboobeh (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The present study aimed to investigate the structural relationship between emotional intelligence and COVID-19 anxiety, considering the mediating roles of perceived social support and social cohesion among university students.Methods and Materials: This research employed a descriptive-correlational design with an applied purpose and field data collection method. The statistical population included all students enrolled in Payame Noor University of Bushehr Province during the second semester of the 2021–2022 academic year (N = 7,900). A sample of 237 students was selected using simple random sampling based on the Morgan table. Data were collected using four standardized instruments: Cron’s Emotional Intelligence Questionnaire (2007), the Coronavirus Disease Anxiety Scale (CDAS), the Multidimensional Scale of Perceived Social Support, and Keyes' Social Well-being Questionnaire (1998). Structural Equation Modeling (SEM) using SmartPLS and SPSS-25 software was used to test the hypothesized relationships.Findings: The results demonstrated that emotional intelligence significantly and negatively predicted COVID-19 anxiety (β = -0.136, t = 2.247, p < 0.05). Perceived social support also negatively predicted COVID-19 anxiety (β = -0.340, t = 6.899, p < 0.001), and emotional intelligence significantly predicted perceived social support (β = 0.496, t = 13.321, p < 0.001). Additionally, emotional intelligence significantly predicted social cohesion (β = 0.534, t = 11.478, p < 0.001), and social cohesion negatively predicted COVID-19 anxiety (β = -0.201, t = 2.927, p < 0.01). The indirect effects of emotional intelligence on COVID-19 anxiety through perceived social support (β = -0.169, t = 5.501) and social cohesion (β = -0.107, t = 2.661) were also significant.Conclusion: The findings highlight the protective role of emotional intelligence in reducing pandemic-related anxiety through the enhancement of perceived social support and social cohesion.